2018
DOI: 10.1039/c8ra05034a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon supported olivine type phosphate framework: a promising electrocatalyst for sensitive detection of dopamine

Abstract: In this study, layered olivine-type LiMnPO4/functionalized-multiwall carbon nanotubes composite is used as an electrochemically active material for the real-time detection of dopamine and extended for the detection of human serum (E48) and rat brain-serum (C7) samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Figure E shows the various pHs of redox peak current responses on the modified electrode, and the results revealed that pH 7 is more favorable for APAP detection. In addition, the linear fitting of E pa and E pc vs different pHs revealed slope values of −0.0468 V/pH (oxidation) and −0.0503 V/pH (reduction) (Figure F), which are close to the actual imaginary value of −0.059 V/pH. , Hence, the optimal pH (pH 7) of 0.05 M PB would be suitable for further electrochemical analyses.…”
Section: Resultssupporting
confidence: 62%
“…Figure E shows the various pHs of redox peak current responses on the modified electrode, and the results revealed that pH 7 is more favorable for APAP detection. In addition, the linear fitting of E pa and E pc vs different pHs revealed slope values of −0.0468 V/pH (oxidation) and −0.0503 V/pH (reduction) (Figure F), which are close to the actual imaginary value of −0.059 V/pH. , Hence, the optimal pH (pH 7) of 0.05 M PB would be suitable for further electrochemical analyses.…”
Section: Resultssupporting
confidence: 62%